Muslim-majority Asian languages: contribution to English - Mohamed Ali, Haja Mohideen (IIUM Press, 2015)
Muslim-Majority Asian Languages Contribution to English presents a modest contribution to the field of sociolinguistics. Loan words in English have been identified as those which may be attributed to languages spoken by majority speakers who are Muslim. While many words in European languages have found their way into English, much research on vocabulary items from Muslim-Majority languages and how they are used in the borrowing language is presumably lacking. The present book hopes to fulfil the need and provide English language users with opportunities to show the vastly global nature of the global lingua franca.